ANALISIS CULTURALLY RESPONSIVE TEACHING FOR MEANINGFULL LEARNING DI SD NEGERI PEPELEGI II - Sari, Della Puspita; Rachmadyanti, Putri; Alfiyah, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in Indonesia today has become a crucial aspect for the younger generation in facing future life challenges. The government has placed significant emphasis on the quality of education to cultivate educated and knowledgeable generations. One of the implementations of this focus is the